Treatment of Patients with Obese Type 2 Diabetes with Tantalus-DIAMOND® Gastric Electrical Stimulation: Normal Triglycerides Predict Durable Effects for at Least 3 Years - Lebovitz, H. E.; Ludvik, B.; Yaniv, I.; Schwartz, T.; Zelewski, M.; Gutterman, D. D.; Metacure Investigators (Hormone and Metabolic Research, 2015)
The objectives of the present work are to evaluate long-term benefit of nonexcitatory gastric electrical stimulation (GES) by the DIAMOND® device on glycemic control and body weight in patients with type 2 diabetes inadequately controlled with oral agents and to determine the magnitude of the modulating effects of fasting plasma triglyceride (FTG) levels on these effects of GES. Sixty one patients with type 2 diabetes [HbA1c>7.0% (53 mmol/mol) to<10.5% (91 mmol/mol)] were implanted with the DIAMOND® GES device and treated with meal-mediated antral electrical stimulation for up to 36 months. The effects of baseline HbA1c and FTG on glycemic control, body weight, and systolic blood pressure were measured. GES reduced mean HbA1c by 0.9% and body weight by 5.7%. The effects were greater in patients with normal fasting plasma triglycerides (NTG) as compared to those with hypertriglyceridemia. The mean decrease in HbA1c in patients with NTG averaged 1.1% and was durable over 3 years of follow-up. ANCOVA indicated that improvement in HbA1c was a function of both baseline FTG group (p=0.02) and HbA1c (p=0.001) and their interaction (p=0.01). Marked weight loss (≥ 10%) was observed in a significant proportion of NTG patients by 12 months of treatment and persisted through the 3 years. GES improves glycemic control and reduces body weight by a triglyceride-dependent mechanism in patients with type 2 diabetes inadequately controlled on oral agents. It is postulated that this is through a gut-brain interaction that modulates effects on the liver and pancreatic islets.
Keywords: diabetes mellitus type 2; HbA1c; hepatic glucose production; body weight; neuropeptides; obesity